(untitled) (Web of Teachers: Inderscience Research, 2026)
This article highlights the significance of the PIRLS international assessment program in our country’s education system and its role in identifying and developing reading literacy among primary school students. Through the PIRLS program, opportunities are created to assess and enhance students’ competencies such as text comprehension, analysis, and evaluation.